The Antiproliferative Properties of Uncaria tomentosa Willd. DC. Extracts Against Caco2 and HeLa Cancer Cell Lines - Shen, Jaixi; Shalom, Joseph; Cock, Ian Edwin (Pharmacognosy Communications)
Introduction: Uncaria tomentosa is used in Central and South American folk medicine to treat a variety of diseases. It is particularly well known for treating cancer and studies have confirmed its activity against some carcinoma cell lines. However, to date, U. tomentosa extracts have only been screened against a limited panel of cancer cells. Methods: Solvent extracts were prepared from U. tomentosa inner bark and their antiprolif erative activities against Caco2 and HeLa cancer cells were determined by an MTS based cell proliferation assay. Toxicity was determined using the Artemia franciscana nauplii bioassay. Results: Methanolic and aqueous U. tomentosa extracts were strong inhibitors of Caco2 and HeLa cell proli feration, with IC50 values generally below 1500 µg/mL. The methanolic extract was particularly effective, with IC50 values of 881 and 763 µg/mL against Caco2 and HeLa cells respectively. In contrast, the mid to lower po larity solvent extractions (ethyl acetate, chloroform and hexane) were less potent inhibitors of cell proliferation. Indeed, exposure of the Caco2 cells to the chloroform and hexane extracts produced proliferation levels equivalent to those of the untreated control. Cell imaging studies detected morphological features consistent with apoptosis in Caco2 cells exposed to the methanolic and aqueous U. tomentosa extracts, indicating that these extracts are functioning by cytotoxic mechanisms. All U. tomentosa extracts were nontoxic in the Artemia franciscana bioassay, with LC50 values sub stantially >1000 µg/mL. Conclusions: The antiproliferative activity of the U. tomentosa inner bark extracts against HeLa and Caco2 cancer cell lines indicates their potential in the treatment and prevention of some cancers.
Keywords: Cat’s claw; Uña de gato; Rubiaceae; Anticancer activity; Antip roliferative activity; Caco2; HeLa; Apoptosis